The Sytactical of structure of Malay and Arabic: contrastive study. - Hassan, Fekri Abidin; Ali, Asem Shehadeh Saleh (Centre for Promoting Ideas, USA, 2011)
This paper tries to contrast the Syntactic structures between Arabic and Malay. The paper starts with an introduction about contrastive study, then descriptive study of some aspects related to syntax of Malay and Arabic, such as word-order, noun phrase, passive voice, object, and sentence, then followed by syntax of Arabic. Arabic structures were studied, the subject of nominal sentence and verbal sentence are described as well as Malay. The study contrasts between both languages by comparing the subject in syntax, and found out some similarities in nominal sentences, conditional sentence and specified the differences in subject NP which immediately dominated by the node S as the subject.